A Sociological Radiography of the Communist Movement from 1921-1923 - Sebastian, Fitzek; Neagu Gabriela; Stănescu Simona Maria; Fitzek Cătălina Daniela (European Journal of Multidisciplinary Studies, 2017)
:In this article I approached the emergence and Comintern origins of the Communist Party of Romania.The conflict between communist leaders and the Romanian State authorities started from the critical Movement position towards the Great Union on 1st of December 1918. Among other causes that led to the conflict was the affiliation of the new party to Comintern. The party subordination to a foreign authority involved a new dilema regarding the sociological concept of political party. In this sense, the research goals were determined by analyzing two factors: a. Comintern beginnings of PCdR; b. the position taken by founding leaders towards the Great Union from 1921 – 1923. As part of the research, I conducted three analysis sets: a. a documentary analysis of the files present in the National Archives of the State; b. a leadership analysis of three key-personalities, who played an important role in the movement’s rise; c. A secondary analysis which for I consulted various articles, books and important studies directly related to this subject.